Paradigm of Community in the Society - Convict's Community (Kriminalističke teme, 2002)
This work analyses a convict's community within the context of criminal, as the community of people that were sentenced and as a result of it are in jail. Jail is a type of a given space which is defined by artificially established borders that are being maintained by walls, laws, rules within which people establish immediate relations that by time receive autonomous forms in the sense of jail subculture. The necessary characteristic of the convict's community is a common given space, which is being socialized, from the side of convict's community in the sense of processes known as "prisonisation". On the basis of that a social product of prison are being analyzed as prison subculture, adaptive strategies, prison status and roles, conflicts and many other specific connected for the circumstances.